2021
DOI: 10.1186/s12942-021-00284-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk and space: modelling the accessibility of stroke centers using day- & nighttime population distribution and different transportation scenarios

Abstract: Purpose Rapid accessibility of (intensive) medical care can make the difference between life and death. Initial care in case of strokes is highly dependent on the location of the patient and the traffic situation for supply vehicles. In this methodologically oriented paper we want to determine the inequivalence of the risks in this respect. Methods Using GIS we calculate the driving time between Stroke Units in the district of Münster, Germany for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…To create the routable network, we used an approach for OpenStreetMap data, based on maximum speeds ( V max ) and surrounding population density (Bundesinstitut für Bau‐ Stadt‐ und Raumforschung im Bundesamt für Bauwesen und Raumordnung, 2019 ; Rauch et al, 2021 ). OSM has large gaps in the presentation of V max in Switzerland (approx.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…To create the routable network, we used an approach for OpenStreetMap data, based on maximum speeds ( V max ) and surrounding population density (Bundesinstitut für Bau‐ Stadt‐ und Raumforschung im Bundesamt für Bauwesen und Raumordnung, 2019 ; Rauch et al, 2021 ). OSM has large gaps in the presentation of V max in Switzerland (approx.…”
Section: Methodsunclassified
“…First, we compared access in rural, intermediate and urban areas, as categorised by the Swiss Federal Statistical Office (2014). Second, we compared Swiss citizens' versus foreign residents' access to PPCs.To create the routable network, we used an approach for Open-StreetMap data, based on maximum speeds (V max ) and surrounding population density (Bundesinstitut für Bau-Stadt-und Raumforschung im Bundesamt für Bauwesen und Raumordnung, 2019;Rauch et al, 2021). OSM has large gaps in the presentation of V max in Switzerland (approx.…”
mentioning
confidence: 99%
“…A variety of studies have indicated options to shorten the time from stroke onset to reperfusion, such as cooperative method (9), workflows in hospitals (10,11), rapid diagnoses (12), and public awareness campaigns (13). However, infrastructure and human resources such as spatial accessibility (14)(15)(16), facilities (i.e., the number of beds, equipment), and human resources (17) are critical. Optimization of supply against demand is a crucial issue because the allocation of facilities and human resources affects the onset-to-reperfusion time in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, classic 2SFCA models have not taken the universal coverage of multilevel healthcare in a large region and extreme long-distance healthcare seeking behavior into account because of the limitation of the inefficient repetitive computing. Moreover, different modes of transportation have gained the attention of many scholars, but the estimation of hospitalization time based on assumed speeds would still bias accessibility, especially in densely populated areas [ 32 ]. How to integrate real-time travel distances into 2SFCA algorithm models and calculate the corresponding hospitalizing weight in further experimental studies is still in process [ 23 ].…”
Section: Introductionmentioning
confidence: 99%